Influence of the track structure on the vertical dynamic interaction analysis of the low-to-medium-speed maglev train-bridge system. Issue 14 (October 2019) - Wang, Dangxiong; Li, Xiaozhen; Liang, Lin; Qiu, Xiaowei
The low-to-medium-speed maglev train is stably suspended near the rated suspension gap. The suspension force acts directly on the track and is transmitted to the bridge. The maglev track structure is novel, and the influence mechanism of the track structure on the coupled vibration of the maglev train-bridge system is unknown. Therefore, in this study, we propose vertical dynamic interaction models of the low-to-medium-speed maglev train-bridge system and the low-to-medium-speed maglev train-track-bridge system to analyse the influence mechanism of the maglev track structure on the vertical dynamic interaction of the low-to-medium-speed maglev train-bridge system. The vibration characteristics of the F-rail and the influence mechanism of the track structure on the dynamic responses of the bridge are discussed in detail. The study verifies that the local deformation of the F-rail is self-evident and cannot be ignored. In addition, the influence of the F-rail on the dynamic interaction of the maglev train-bridge system is mainly reflected in two aspects: first, the vibration of the bridge in the high-frequency band increases due to the high frequency and intensive local vibration of the F-rail itself. Second, the vibrations of the bridge and the F-rail in the low-frequency band increase due to the periodic irregularities caused by the local deformation of the F-rail. In this study, we consider the vertical dynamic interaction model of the low-to-medium-speed maglev train-track-bridge system.